PENERAPAN TEKNIK MENGKLARIFIKASI NILAI (VALUE CLARIFICATION TECHNIQUE) UNTUK MENINGKATKANPEMAHAMAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Martoni, Martoni; Andrizal, Andrizal; Akbar, Helbi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The subject of Islamic Education is a subject that focuses on the affective domain or attitude which consists of a vehicle for planting values, morals, and standard norms such as social sense, nationalism, and even a belief system. From the results of interviewing researchers with one of the PAI teachers, it was found that there were several problems in learning Islamic Religious Education including: Students had difficulty understanding Islamic Education subject matter, especially on material, imitating the attitude of Prophet As, Prophet Musa and Prophet Isa. Students also feel bored and bored in learning so that students do not interpret the learning process. The data in this study were obtained from observation, interviews, tests and documentation, with 8 students consisting of 3 men and 5 women. The results of the research on the implementation of the value clarification technique were proven to be able to improve the learning comprehension of fifth grade students in PAI subjects at SD N 003 Lubuk Kebun Logas Tanah Darat District. This can be seen from the results of the Pre-Cycle test of only 25%, Cycle I rose to 41.7%, Cycle II rose to 75% and Cycle III had reached 87.5% in PAI subjects at SD N 003 Lubuk Kebun Logas Tanah District Land.Keywords: Value Clarification Techniques; Learning Understanding.